Impact of sterilization and chemical fertilizer on the microbiota of oil palm seedlings - Ding, Joyce Yoon Mei; Ho, Li Sim; Ibrahim, Julia; Teh, Chee Keng; Goh, Kian Mau (Frontiers in Microbiology, 2023)
Soil nutrients and microbiota are known as essential components for healthy plant growth and crop productivity. However, limited studies have been conducted on the importance of soil microbiota in the early growth of oil palm seedlings (Elaeis guineensis Jacq.) under the influence of NPK compound fertiliser (nitrogen, phosphorus, and potassium). In this study, we analysed the root microbial community associated with seedlings grown under normal and sterilised soil conditions to ascertain the microbial strains potentially associated with soil, plant health and chemical fertiliser efficiency. Oil palm seedlings were grown under four treatments: (i) fertilised normal soil (+FN), (ii) unfertilised normal soil (FN), (iii) fertilised sterilised soil (+FS) and (iv) unfertilised sterilised soil (FS). Our findings revealed that chemical fertiliser promoted the growth of the copiotrophs Pseudomonadota and Bacteroidota in the control +FN, which are known to degrade complex polysaccharides. After autoclaving, the soil macronutrient content did not change, but soil sterilisation reduced microbial diversity in the +FS and FS treatments and altered the soil microbiota composition. Sterilised soil with a depleted microbial population adversely affected crop growth, which was exacerbated by fertiliser use. In the rhizosphere and rhizoplane compartments, a total of 412 and 868 amplicon sequence variances (ASVs) were found depleted in the +FS and FS treatments, respectively. Several genera were identified in the ASVs with diminished abundance, including Humibacter, Microbacterium, Mycobacterium, 1921-2, HSB OF53-F07, Mucilaginibacter, Bacillus, Paenibacillus, and several unclassified genera, suggesting their possible roles in promoting the plant growth of oil palm seedlings. Soil sterilisation might remove these beneficial microbes from the bulk soil pool, affecting the colonisation ability in the rhizocompartments as well as their role in nutrient transformation. Therefore, this study provides useful insights concerning the benefits of a soil microbiome survey before making fertiliser recommendations.